Comparative genomics reveals the genomic basis of race T2 emergence and heavy metal resistance in Xanthomonas euvesicatoria pv. perforans - Huang, Chien-Jui; Wu, Ting-Li; Lin, Yu-Han; Lin, Yao-Cheng (Frontiers in Microbiology, 2026)
Bacterial spot poses a significant threat to global pepper and tomato production. Recent phylogenomic analysis of whole genome sequences has revealed that solanaceous bacterial spot-causing xanthomonads belong to five distinct phylogenetic lineages within three species, including two pathovars within Xanthomonas euvesicatoria, X. hortorum pv. gardneri, and X. vesicatoria. X. euvesicatoria pv. perforans (Xep) strains are highly diverse and have become predominant in many tomato production regions. In this study, recently emerged Xep strains from Taiwan were assigned to tomato race T2 based on differential cultivar phenotyping, with effector genotyping used as supporting predictors. To clarify the genomic features of these Xep T2 strains, high-quality genome sequences of two representative isolates were generated and performed comparative genomic analyses were conducted. The T2 phenotype of these strains were supported by the absence and presence patterns of race-associated effector genes in the genome assemblies. Comparative analysis against published Xep genomes revealed plasmid diversity, the evolution of copper resistance, and signatures of horizontal gene transfer in these Xep T2 strains. Notably, a region containing a complete set of copper and heavy metal resistance genes was integrated into the chromosome, providing evidence on evolution of copper resistance in Xep strains in Taiwan. Accordingly, these findings suggest that horizontal gene transfer, including lysogenic conversion, and genetic recombination contribute to the ongoing diversification of X. euvesicatoria pv. perforans and may facilitate adaptation and persistence in tomato production agroecosystems.